1989
DOI: 10.1182/blood.v74.6.2144.bloodjournal7462144
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human granulocyte colony-stimulating factor as an activator of human granulocytes: potentiation of responses triggered by receptor- mediated agonists and stimulation of C3bi receptor expression and adherence

Abstract: Recombinant human granulocyte colony-stimulating factor (rhG-CSF) enhanced superoxide release and membrane depolarization in parallel in human granulocytes stimulated by the receptor-mediated agonists, N- formyl-methionyl-leucyl-phenylalanine and wheat germ agglutinin, but not by the Ca2+ ionophore ionomycin and phorbol myristate acetate, which bypass the receptors to stimulate the cells. The optimal effect was obtained by pretreatment of cells with 25 to 50 ng/mL (1.3 to 2.6 nmol/L) rhG-CSF for 10 minutes at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
27
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 0 publications
5
27
0
Order By: Relevance
“…Preparation of neutrophils. Peripheral blood neutrophils from healthy adult donors were prepared as described previously (Yuo et al, 1989b), using dextran sedimentation, centrifugation with Conray±Ficoll and hypotonic lysis of contaminated erythrocytes. Neutrophil fractions were suspended in Hanks' balanced salt solution (HBSS) and contained more than 98% neutrophils.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preparation of neutrophils. Peripheral blood neutrophils from healthy adult donors were prepared as described previously (Yuo et al, 1989b), using dextran sedimentation, centrifugation with Conray±Ficoll and hypotonic lysis of contaminated erythrocytes. Neutrophil fractions were suspended in Hanks' balanced salt solution (HBSS) and contained more than 98% neutrophils.…”
Section: Methodsmentioning
confidence: 99%
“…Determination of neutrophil functions. The superoxide (O 2 2 )-releasing capacity was determined by SOD-inhibitable reduction of ferricytochrome c as described previously (Yuo et al, 1989b). For the end-point assay, the cell suspension in HBSS was added to each well of the 48-well plate (Falcon no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro and ex vivo studies have shown that G-CSF primes human PMN and enhances respiratory burst superoxide (O ÿ 2 ) release stimulated by the chemotactic peptide N-formylmethionylleucylphenylalanine (FMLP) Yuo et al, 1989;Sullivan et al, 1993).…”
mentioning
confidence: 99%
“…Surface expression of the 2 integrin (CD11b/CD18) has been reported to be either unchanged (Spiekermann et al, 1994) or up-regulated both in vitro and ex vivo Yuo et al, 1989;Yong & Linch, 1992).…”
mentioning
confidence: 99%